If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 6) = 2x + -5 Reorder the terms: 3(6 + x) = 2x + -5 (6 * 3 + x * 3) = 2x + -5 (18 + 3x) = 2x + -5 Reorder the terms: 18 + 3x = -5 + 2x Solving 18 + 3x = -5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 18 + 3x + -2x = -5 + 2x + -2x Combine like terms: 3x + -2x = 1x 18 + 1x = -5 + 2x + -2x Combine like terms: 2x + -2x = 0 18 + 1x = -5 + 0 18 + 1x = -5 Add '-18' to each side of the equation. 18 + -18 + 1x = -5 + -18 Combine like terms: 18 + -18 = 0 0 + 1x = -5 + -18 1x = -5 + -18 Combine like terms: -5 + -18 = -23 1x = -23 Divide each side by '1'. x = -23 Simplifying x = -23
| 8/4a | | 2x^3-3x^2-32x-15=0 | | 1/4a=12 | | 32x+74=10 | | 14-8x=58-22 | | x^2-10-24=0 | | 12x^4+10x^3+6x^2=0 | | 22x+15=533 | | (7y^2-5y+4)-(2y^2-5y+7)= | | 3/4y-5=-1+1/4y | | 8-y/2=5-9 | | 56-2x=7x+21 | | 3/4k-5=-1+1/4 | | 6*x/2=4*x/2 | | 2x-4+3(x-2)=0 | | (9y^2+5y+2)-(2y^2-5y+9)= | | 2/3(a-2)+6=18 | | C/5=4 | | x^2+6x-97=0 | | 6(x+5)=-4x+6+2x | | 4.5/18 | | 3x-5(x+3)=2x+15 | | 5(3x-5)-7(2x+5)+9(3x-2)= | | x+5+x-2=54:15 | | x+5=54 | | (6y^2-5y+6)-(9y^2-5y+7)= | | -1.4-(0.2x+3)=0.8x-1.2 | | 4x^2+18x-1882=0 | | x+5+x-2=54-15 | | -5=x+10 | | x+5+x-2=54 | | 6(5x+4)+2(3x-7)-5(7x-4)= |